Scaling and sustaining CIS and CSA through Bundled Business Models - Prager, Steven D.; Byandaga, Livingstone; Kagabo, Desire M. (2021)
Bundling agricultural innovations associated with CSA with other services such as climate information and financial services (e.g., combining crop varieties that resist drought or heavy rains with recommendations regarding best practices with access to insurance) is a key means to improve our ability to face these compound challenges. The synergistic nature between CIS and CSA - and the potential complementarity of each to support the scaling of the other – raises an important question. How can CIS and CSA be bundled together with other agriculture products and services to support sustainable scaling in the delivery of the same? In other words, what are the business models that can support the implementation of CIS and CSA in a manner that maximally benefits farmers and does so in a way that is profitable for private sector implementing partners? This policy brief unpacks this question by examining a few exemplary cases and characterizing each in relation to seven different assessment categories. These categories spanning core technologies to available evidence provide perspective on each case and the components that may contribute to potentially scalable business models.